STUDI LITERATUR: PENGGUNAAN MEDIA VIDEO ANIMASI CERITA RAKYAT UNTUK KETERAMPILAN BAHASA PESERTA DIDIK SEKOLAH DASAR - Nursanti, Aprilia; Farida Ariyani; Ryzal Perdana (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Indonesian language learning at the elementary school level still faces various challenges in improving students' listening, reading, writing, and storytelling skills. One alternative that can be implemented is the use of animated video media, which has been proven to enhance motivation and learning outcomes. This study aims to examine the effectiveness of animated videos in Indonesian language learning by referring to ten previous studies. This research employs a literature review method by analyzing ten articles discussing the use of animated videos in Indonesian language learning. Various testing methods used in previous studies include pretest-posttest, t-test, expert validation, and N-Gain analysis. The analysis results indicate that animated videos significantly contribute to improving students' language skills. Several studies report an increase in students' learning scores by 78%-90%, with a significant difference between the experimental class using animated videos and the control class applying conventional methods. Additionally, this media has been proven to enhance students' interest, motivation, and comprehension of learning materials. However, challenges in its implementation include limited technological infrastructure in schools and teachers' readiness to utilize this media optimally.